Analisis Semantik pada Puisi "Bunga Gugur" Karya W.S. Rendra - Fadilla Aura Ramadani; Ela Emayusnita Sirait; Erfriani Sekar Talenta Simangunsong; Yuliana Sari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to examine the meanings contained in the poem "Bunga Gugur" by W.S. Rendra using a semantic approach. Poetry was chosen as the object of study because of its ability to reflect human life and feelings through poetic symbols and language. The analysis focused on four types of meaning in semantics, namely lexical, grammatical, referential, and figurative meaning. The research method used is qualitative descriptive with literature study techniques. The results of the analysis show that this poem is rich in lexical and figurative meanings, which strengthen the message of loss, love, and the transience of life. The use of symbols such as "bunga", "gugur", and "asmara" emphasizes the emotional devastation caused by death. With a semantic approach, the hidden meaning in the poem can be revealed systematically, thus helping readers understand the depth of the message the poet wants to convey. This research is expected to enrich linguistic studies in the analysis of literary works and increase appreciation for modern Indonesian poetry.